Liability of Mining Companies Related to Environmental Pollution in the Perspective of Prophetic Law: Pertanggungjawaban Perusahaan Tambang Terkait Pencemaran Lingkungan dalam Perspektif Hukum Profetik - Suciati, St. Muslimah; Sarif, Asri; Rasmuddin; Arfa, Arfa (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to analyze aspects of mining company liability related to environmental pollution in the perspective of prophetic law. A review of prophetic law is used as an analytical knife to confirm the existence of prophetic law, one of which emphasizes